Karakterisasi Biogas Hasil Pemurnian dengan Down-Up Purifier Termodifikasi - Ritonga, Abdul Mukhlis; Masrukhi, Masrukhi; Safi’i, Azis Imam (Jurnal Rekayasa Mesin, 2021)
Biogas is a combustible gas produced from the fermentation process of organic materials by anaerobic bacteria. Biogas can be made by using a digester. A digester is a place where the process of decomposing organic matter by bacteria. The result of biogas still contains impurity gases, so that the quality of biogas is not good. Therefore, efforts to filter the gas are necessary. The purifier is a device to filter a gas. The use of purifiers in a series of digester installations aims to filter out unnecessary gases. The purpose of this research is to design a down-up purifier type biogas purification plant, to determine the changes in substrate characteristics during fermentation and conduct a gas quality test after purification. The results showed that the biogas installation type down-up purifier was designed and assembled using 150 liter drums for gas digesters and reservoirs, 1/2 inch hoses for connecting, 2 purifiers for purification and activated charcoal adsorbents. The C/N ratio is 36.37, an average substrate temperature of 28.62oC and an average pH of 5.9. Initial and final Biological Oxygen Demand (BOD) values are 960.12 mg/l and 9.312.53 mg/l. The initial and final Chemical Oxygen Demand (COD) values are 313,500.00 mg/l and 29,100.00 mg/l. Then Total Solid (TS) decreased by 1.45% and Volatile Solid (VS) increased by 0.21%. The use of activated charcoal adsorbents in the two purifiers can reduce CO2 gas content by 83.79% in biogas with the most optimal purification time of 60 minutes.